Perfil dermatoglífico, somatotípico e fisiológico de atletas de elite do rafting - Takehara, Julio Cesar (2016)
Rafting is a modality that is summed up in the descent of rivers in inflatable boats, in which the members of the boat paddle under the command of an instructor responsible for the orientation of the group during the course, in leisure and tourism activities. However, when it comes to competition, rafting can be practiced by female or male teams, with an initial age of 15 years, in competitions held in three days of events, and in R6 and R4 modalities. The objective of this research was to identify the dermatoglyphic profile, the body composition, the somatotype, the motor tests, the lipid profile, the glycemic and the ergospirometry profile of the elite rafting athletes. Participants were seven male athletes with 21.5 ± 0.5 years, of the sub-23 category. Dermatoglyphic characteristics were evaluated by computerized scanning, body composition by Bio impedance InBody 720, and somatotropy by anthropometric measurements. The motor tests were abdominal, arm support, vertical thrust, Shuttle-run test and aerobic power by ergospirometry in adapted ergometer rowing. The normality test of Shapiro Wilk was used, after applying the Pearson correlation coefficient for the variables, considering a significant value of p <0.05. The athletes presented in the fingerprints 9% of arches, 19% of whorls and 72% of loops, still an average of 112.7 ± 29.9 LQTS and 10.7 ± 2.1 D10; Mean body mass of 72.3 ± 6.9 kg; Height 174.8 ± 7.2 cm; BMI 23.7 ± 1.7 kg/m2, endomorph components 2.6 ± 0.8, mesomorph 5.4 ± 1.3, ectomorph 2.2 ± 0.9, percentage of fat 10.0 ± 4.8 %, Fat mass 7.4 ± 4.1 kg, lean mass 64.9 ± 5.4 kg and skeletal muscle mass 35.5 ± 3.0 kg. The mean load for ergospirometry was 100.0 ± 17.9 W and the maximum oxygen consumption of 66.2 0.8 ml.kg-1.min-1, the production of carbon dioxide 79.6 ± 1, 5 ml.kg-1.min-1, the maximum ventilation 96.9 ± 2.2 l.min-1 respiratory quotient at the time of fatigue 1.2 ± 0.0 and the maximum heart rate 198.5 ± 05 bpm. Blood glucose was 83.7 ± 6.5 mg/dl, cholesterol 169.0 ± 32.7 mg/dl, triglycerides 71.0 ± 15.3 mg/dl and creatinine 1.0 ± 0.1 mg/dl. In the abdominal test 57.0 ± 12.7 repetitions, in the arm support 59.7 ± 13.7 repetitions, in the vertical impulse 51.2 ± 8.6 cm, in the agility 11.5 ± 1.1 seconds. There were strong positive correlations (r> 0.75) for the variables VO2max and VO2max, clamp and MME, veticilo and age, veticilo and VO2max, D10 and age, D10 and MME, SQTL and age. And strong negative correlations (r> -0.75) between the whorl and endomorph component and D10 and endomorph component. It is concluded that the identification of dermatoglyphic profile, body composition, somatotípia, biochemical, motor tests and ergo-spirometry of athletes of high-performance rafting can be applied directly in the orientation of the training strategies, of the various physical qualities involved in this sport, As an auxiliary measure to physical training. This statement is based on the results presented here that reflect the profile of the high performance in the modality, and which, in turn, suggest the predisposition of a subject to said sport.